0.18 mW/pole inverter‐based Gm‐C bandpass filter with automatic frequency tuning. Issue 15 (1st July 2018) - Zhou, Mingzhu; Wang, Keping
Abstract : A low‐power Gm ‐C filter with the elliptic prototype targeting wireless application of the IEEE 802.15.4 (ZigBee) standard is presented. A modified inverter‐based Gm cell is proposed to increase the current efficiency. Due to the tail current source, this Gm cell also shows better common‐mode rejection and power supply rejection performance than traditional operational transconductance amplifier (OTA) structure. The filter is implemented in a 65 nm CMOS process. It achieves a figure of merit of 0.01 fJ with a power consumption of 0.18 mW/pole from a 1.2 V supply voltage. It provides stopband attenuation better than 40 dB, and an in‐band IIP3 of 9 dBm. An automatic frequency tuning circuit based on sine‐wave PLL method is introduced to compensate for the process variations. The centre frequency and bandwidth can be simultaneously tuned to satisfy the specifications. They are also stable over the process variations with only 2.3% deviation.